KONTRAK STANDAR: ANTARA PRINSIP KEHATI-HATIAN BANK DAN PERLINDUNGAN NASABAH DEBITUR - Paripurna P. Sugarda (Fakultas Hukum Universitas Gadjah Mada, 2008)
The existence of standard contract or standard agreement are something that we have to accept. It might be an efficient, practical, fast and effective way for business people. It can bring many advantages, particularly for a mass production of contract which requires a standard for such contract. On the other side, consumer for instance, it is an option which less favorable since he has to decide which option he is going to take it or leave it. Therefore, on a standard contract, the less the chance for opposite party to negotiate or to amend any clauses on such contract. This paper will answer three question, that is, the first, how does Indonesian law implement prudential principle in loan contract. The second, why does standard contract has many weakness. The third, how does Indonesian Banking implement prudential principle on standard contract which they make.